Perinatal outcome in pregnancies associated with hypertension: A prospective cohort study in a rural tertiary care teaching hospital of North India - Indu Verma; Charvi Chugh; Dinesh Sood; R K Soni (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of the study is to know type of hypertension affecting pregnant women and impact on perinatal outcome. Subject and Methods: This is a prospective cohort study; 120 women with hypertensive disorders of pregnancy (HDP) at gestation ≥28 weeks who delivered in our institute were enrolled. Sociodemography, gestational age, mode of delivery, APGAR, birth weight, fetal growth restriction (FGR), and perinatal outcome were recorded. Mean ± standard deviation or proportions, analysis of variance, Chi-square test, and odds ratio were used for statistical analysis. Results: Preeclampsia (PE) was most prevalent hypertensive disorder of pregnancy (44.2%), followed by eclampsia (27.50%), gestational hypertension (23.3%), and chronic hypertension (CH) (5.0%). In PE group, 61.8% had FGR, 65.5% newborns were preterm, 74.6% had low birth weight, and 54.1% needed neonatal intensive care unit (NICU) admission. In eclampsia group, 42.9% had fetal growth restriction, 65.7% preterm, 80% low birth weight, and 78.6% NICU admission. PE women delivered more fetal growth-restricted babies with odd ratio of 2.37 (95% confidence interval [CI]: 1.15, 4.9) and at lower gestation with odd ratio of 2.00 (95% CI: 0.95, 4.21). Eclampsia group had more newborn with low APGAR 1 min, NICU admissions, and those requiring ventilator with odds ratio of 3.10 (95% CI: 1.37, 7.03), 4.48 (95% CI: 1.64, 12.24), and 4.09 (95% CI: 1.6, 10.46), respectively. Perinatal mortality was 10, 9, and 2 in eclampsia, PE, and gestational hypertension groups, respectively, with overall rate of 16.9%. PE and eclampsia comprised 71.70% of HDP but contributed 90.5% of all perinatal deaths. Conclusion: Preeclampsia-eclampsia is associated with increased risk of adverse perinatal outcomes as compared to gestational and CH, necessitating screening, vigilant antenatal care, timely intervention, and referral.